Local dynamics of an equation with long delay feedback - D. V. Glazkov (Моделирование и анализ информационных систем)
We study the local dynamics of a nonlinear complex DDE with large delay in the vicinity of the zero solution. The quasinormal forms method is used for the problem analysis. We show that parabolic type GL-equations act as normal forms in critical cases of the infinite dimension.